Relationship between clonal evolution and drug resistance in bladder cancer: A genomic research review - Zhouting Tuo; Ying Zhang; Dengxiong Li; Yetong Wang; Ruicheng Wu; Jie Wang; Qingxin Yu; Luxia Ye; Fanglin Shao; Dilinaer Wusiman; Yubo Yang; Koo Han Yoo; et al. (Elsevier, 2024)
Bladder cancer stands as a prevalent global malignancy, exhibiting notable sex-based variations in both incidence and prognosis. Despite substantial strides in therapeutic approaches, the formidable challenge of drug resistance persists. The genomic landscape of bladder cancer, characterized by intricate clonal heterogeneity, emerges as a pivotal determinant in fostering this resistance. Clonal evolution, encapsulating the dynamic transformations within subpopulations of tumor cells over time, is implicated in the emergence of drug-resistant traits. Within this review, we illuminate contemporary insights into the role of clonal evolution in bladder cancer, elucidating its influence as a driver in tumor initiation, disease progression, and the formidable obstacle of therapy resistance.